The New World genus Rhinoleucophenga (Diptera: Drosophilidae): new species and notes on occurrence records - Poppe, Jean Lucas; Schmitz, Hermes José; Valente, Vera Lúcia Da Silva (Zootaxa, 2015)
The genus Rhinoleucophenga Hendel comprises 26 nominal species with New World distribution. In the present study, two new species are described from samples in the Pampa and Caatinga biomes in Brazil, R. punctuloides sp. nov. and R. trivisualis sp. nov., respectively. Rhinoleucophenga punctuloides sp. nov. is a sibling species of R. punctulata Duda. Furthermore, two females of R. joaquina Schmitz, Gottschalk & Valente were found for the first time and a description is presented. A taxonomic dichotomous key with pictures is given for the Rhinoleucophenga species recorded in the Caatinga and Pampa biomes. The Neotropical open environments are areas of high diversity for Rhinoleucophenga. The description of new species and review of some older descriptions can change the area of species distribution and improve the faunistic knowledge of other localities in which previous studies have shown unidentified or misidentified Rhinoleucophenga species.